Mastering Real-Time Data Processing Applications : Optimization Strategies for Peak Performance - Mohammed Naseer Khan (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores strategies for optimizing real-time data processing applications in the era of big data and distributed systems. It examines the growing demand for real-time analytics across industries and organizations’ challenges in maintaining low latency and scalability. The article discusses key optimization techniques, including leveraging the Akka framework’s actor model and supervision strategies, implementing efficient data ingestion through stream processing and partitioning, utilizing caching strategies, employing robust monitoring and auto-scaling mechanisms, ensuring fault tolerance through checkpointing and graceful degradation, and adopting asynchronous communication patterns. Throughout the article, real-world case studies and performance metrics demonstrate the significant improvements these strategies can bring to system throughput, latency, and resilience in various sectors such as finance, e-commerce, telecommunications, and manufacturing.